Entrepreneurship Technology (ENT600) Ergonomic wheelbarrow / Amsyar Wajdi Ismail, Muhamad Helmi Affandi Adnan and Mohammad Zarriq Adzrin Mohd Pooad - Ismail, Amsyar Wajdi; Affandi Adnan, Muhamad Helmi; Mohd Pooad, Mohammad Zarriq Adzrin (2017)
The product to be developed is an ergonomic wheelbarrow. The ergonomic wheelbarrow developed to ease the burden of people while carrying load as well as taking care of consumer health. The name of this wheelbarrow seemly matched with the main function because this ergonomic wheelbarrow help to prevent consumer from lower back pain because of carrying heavy load. Ergonomic wheelbarrow will be sold to the three main party. The three main party are Construction Company, Landscape Company and home owner. This is the main target buyer for our product. With the rapid growth of this wheelbarrow use, the product offers tremendous advantages as well as the thousands of other workers assigned the responsibility of carrying loads for any project every day. This product will be positioned as a high-end equipment which enables workers to carry more loads in a time via advancement made to the amount of tires being install for the purpose of improving stability and absorbing shock. There is currently no other company that produces this type of wheelbarrow with the functional features we are going to develop. It will be sold in retail markets with both traditional selling which in physical store and online website. It also will be promote in our company website so buyer can do research which read all description and advantages of our product before buying this ergonomic wheelbarrow. This ergonomic wheelbarrow will be sold in the market with price RM600. This price is reasonable to compare with its function. It 4s because the packages come with the ergonomic wheelbarrow are worth it.